Efektivitas Ekstrak Kloroform Caulerpa racemosa Dalam Menghambat Pertumbuhan Bakteri Patogen Penyebab Infeksi Saluran Pernapasan Akut (ISPA) - Sriyati Sampulawa; Ali Awan; Dominggus Rumahlatu (Jurusan Biologi FMIPA Universitas Cenderawasih, 2017)
Acute respiratory infection is a serious health problem in the world and in Indonesia. Acute respiratory infection is caused by a variant of the bacteria and resistance to antibiotics. The Latest researches on antibacterial compounds based on natural ingredients have been conducted. One of them is derived from green algae. This study aims to determine the antibacterial activity of green algae Caulerpa racemosa extract in inhibiting the growth of pathogenic bacteria causing acute respiratory infection. This study includes an extraction process using chloroform. Antibacterial testing was done by using a concentration of 0.5%, 1%, 5%, 10%, 20%, 40%, 60% and 80%, in order to obtain the minimal Inhibitory Concentration. The results showed that C. racemosa extract was able to inhibit the growth of test bacteria Streptococcus mitis, Bacillus anthrachis, and B. cereus, with the best activity at concentration of 0.5% and 80%. Meanwhile the extract did not have the activity to inhibit the Gram-negative bacteria. Phytochemical test showed that chloroform of C. racemosa extract contain steroids and terpenoids compounds capable of inhibiting the growth of testing bacteria. Key words: antibacterial activity, C. racemosa, pathogenic bacteria, Acute respiratory infection